2014
DOI: 10.1097/bpo.0000000000000119
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Trigger Thumb Release in Children

Abstract: Level II therapeutic study-prospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 18 publications
1
23
0
2
Order By: Relevance
“… 49 - 56 Throughout the literature review, we found no studies published on the treatment of PTF with steroid injections or percutaneous release; however, there were some studies published over the percutaneous release of trigger thumb. 19 , 21 , 57 Masquijo and colleagues 19 concluded that percutaneous release of the paediatric trigger thumb was not safe due to risk of iatrogenic injury to nerves and vessels as well as the possibility of an incomplete release of the A1 pulley. Due to differences in the underlying pathology of PTF and adult trigger finger, these methods of treatment may not be appropriate in the treatment of children.…”
Section: Discussionmentioning
confidence: 99%
“… 49 - 56 Throughout the literature review, we found no studies published on the treatment of PTF with steroid injections or percutaneous release; however, there were some studies published over the percutaneous release of trigger thumb. 19 , 21 , 57 Masquijo and colleagues 19 concluded that percutaneous release of the paediatric trigger thumb was not safe due to risk of iatrogenic injury to nerves and vessels as well as the possibility of an incomplete release of the A1 pulley. Due to differences in the underlying pathology of PTF and adult trigger finger, these methods of treatment may not be appropriate in the treatment of children.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report on 15 pediatric subjects treated with percutaneous followed by open release found that the A1 pulley was incompletely released in 30% of cases after the percutaneous release, whereas 80% were complicated by lacerations to the flexor tendons. 22 No neurovascular injuries were seen but the mean distance between the needle used for the percutaneous release and the radial digital nerve was only 2.5 mm. This suggests that percutaneous release may not be appropriate for the pediatric trigger thumb.…”
Section: Trigger Thumbmentioning
confidence: 98%
“…Se ha demostrado que es una alteración del desarrollo, 9,2,1 porque al nacimiento el tendón es de tamaño normal, pero en los primeros 3 años de vida se va engrosando. 10,11,9 En 25 a 30% de los casos ocurre afectación bilateral, 2 aunque no suele manifestarse al mismo tiempo. 5 Existen reportes de familias que muestran un patrón de herencia dominante con penetrancia variable, 7 pero no existe predisposición por género; a diferencia del resto de los dedos, el pulgar en gatillo no se relaciona con alteraciones sistémicas.…”
Section: Figuraunclassified
“…8 La cirugía consiste en realizar un acceso transverso de 1 cm sobre el pliegue palmar de la articulación metacarpofalángica y un corte longitudinal en la polea A1; no es recomendable efectuar liberaciones percutáneas, porque se asocian con índice de falla de 30% al no liberar por completo la polea y lesión parcial del tendón en 80% de los casos. 10 La referencia al ortopedista pediatra debe hacerse ante cualquier sospecha o al establecer el diagnóstico, pero la mayoría de los pacientes se beneficia del tratamiento quirúrgico.…”
Section: Figuraunclassified